Corporate Response to Climate Change: What do Stakeholders Expect? - M. S.V. Prasad; B. Sandhya Sri (Australasian Accounting, Business and Finance Journal, 2008)
This paper examines different perceptions on climate change management and disclosures from the viewpoint of stakeholders in Indian Corporations. The paper shows how climate change strategies and disclosures at different organizational levels can be linked to the societal and competitive contexts that companies face, embedded in a stakeholder view. Companies are divided according to certain attributes - location, geographical spread, industry, degree of vertical integration and diversification, companies prioritizing particular stakeholder groups, and their climate change strategies and disclosures including internal measures, supply-chain measures and/or market-based measures that move beyond the supply chain are analyzed. This paper attempts to illustrate how institutional, resource-based, supply chain and stakeholder views are all important to characterize and understand corporate strategic responses to a sustainability issue.
Keywords: climate change; corporate response; stakeholders; perception; environmental accounting; India